Gross negligence and its interference with the state of São Paulo prisons turnovers: an analysis stemmed from DEECRIM – 2aRAJ sentences - Bruno Barros Mendes (Revista Brasileira de Direito Processual Penal, 2021)
This paper aims to explain what disciplinary action in the Brazilian prison system is, as well as what violations of rules and infractions are in terms of the Law of Penal Actions, how they are classified and their consequences during the execution of the conviction decisions. Furthermore, this paper presents a consistent empirical research in the analysis of proceedings judged by the State Criminal Division of the 2nd Circuit Court (DEECRIM-2aRAJ), referred to the Court of Justice of the State of São Paulo, aiming to denote that the disciplinary actions (in administrative and judicial proceedings) violate prisoners human rights and fundamental guarantees. Through access to the Court of Justice of the State of São Paulo electronic portal, it was possible to select the analyzed proceedings here presented and demonstrate the mismatch between the procedures provided in law and the applied practice in the prisons. In conclusion, comparing the results obtained in the research with the official reports issued by the National Prison Department, the outcome is that, this critical distance between the force and the effectiveness of the human rights and fundamental guarantees, characterized by the Judicial Power aloofness concerning the prison population, interferes with the local prisons turnovers.